Nuclear Safety and Security in the Arctic: Crafting an Effective Regional Governance System - Lysenko, Mikhail; Vylegzhanin, Alexander; Young, Oran (Arctic Review on Law and Politics, 2022)
The Arctic is saturated with nuclear facilities bringing both benefits for regional economic and social development and risks of nuclear and radiological accidents and concerns about radioactive wastes. There is every reason to expect the Arctic will remain a nuclearized region during the foreseeable future. This makes it important to direct attention to issues of nuclear safety and security in the region. We identify several clusters of these issues in the Arctic, including the challenges of potential nuclear accidents, the handling of spent nuclear fuel and radioactive waste, the cleanup of radiological contaminants, and concerns about nuclear security. An analysis of international conventions and voluntary codes of conduct shows that they are applicable to Arctic nuclear safety and security, but only in general terms. This suggests a need for an Arctic-specific agreement on nuclear and radiological safety, emergency preparedness and response, and cleanup of radiological contaminants. The outbreak of military hostilities in Ukraine in February 2022 has disrupted normal procedures for addressing issues of common concern in the Arctic. But the need for co-operation regarding matters like nuclear safety and security will not go away. Assuming it is possible to devise “necessary modalities” for restarting the work of the Arctic Council following the acute phase of the Ukraine crisis, an Arctic-specific agreement on nuclear safety and security could be developed under the auspices of the Arctic Council, which already has taken an interest in nuclear safety through the activities of its Working Group on Emergency Prevention, Preparedness and Response. Once such an agreement is in place, it will become important to consider the infrastructure needed to ensure that its provisions are implemented effectively.